The Impact of Psychological, Social, Societal, and Economic Factors Leading to Relapse in Patients Recovered from Addiction - Jasim Mohammed Hashim Al-Musway (Wolters Kluwer Medknow Publications, 2024)
Background: The problem of using psychotropic substances and addiction has become one of the major problems in the world. Despite the significant increase in treatment programs of addiction, many studies indicate that the rate of relapse globally is very high, especially when treatment is limited to the medical side only. Aims: The study aims to determine the percentage of influence of psychological, societal, social, economic, and other factors that lead to relapse when recovering from addiction. Methods: This study conducted in two main hospitals for the treatment of substance use disorders in Baghdad (Ibn Rushud Teaching Hospital for Psychiatry and Al-Ataa Center for Addiction Treatment) through the period from January 10, 2023, to June 10, 2023. All (300 inpatient) who are suffering from relapse to addiction after recovery were included in the study. The scale was prepared for the psychological, social, therapeutic, environmental, and economic factors, which was used by a group of senior doctors working in the field of treatment of addiction and rehabilitation centers, who unanimously agreed with their expertise on these factors. Results: This study revealed that the most important factor for relapse is the availability of addictive substances (91%); other factors include psychological, social pressures that the addict is exposed to in his social environment, in addition to the loss of social support (76%). The pressure of friends or peers with a rate of (78%) and the weakness of family control (44%) in addition to the influence of other factors that were examined in this study. Conclusion: There are many factors affecting the return of those recovering from addiction to addiction again, and the most prominent of these factors is the abundance or ease of access to psychoactive substances in addition to other factors, which include (psychological, social, societal, and economic factors). Society must realize that the responsibility for preventing addiction should not be borne by the medical treatment alone, because it is a problem that must be dealt with collectively by all parties to enable recovered patients from addiction to build their lives with confidence.